Implementasi Metode Combinative Distance-Based Assessment (CODAS) Untuk Rekomendasi Rekanan Jasa Konsultansi Berbasis Website - Neneng Suriati; Dwi Marisa Midyanti; Uray Ristian (JURIKOM (Jurnal Riset Komputer), 2022)
Regional Research, Development and Innovation (PPID) is one of the fields in the Planning, Development, Regional, Research and Development Agency (BAPPEDALITBANG). The PPID sector at the Kubu Raya Regent's Office has a program to select consulting services. However, the implementation of the selection of consulting services is still done manually by giving each participant a score based on predetermined criteria and the files that have been collected. These values are then added up manually and ranked. The basis for assigning value to participants in consulting services needs to be managed so that the assessment is more effective and structured. Storage of administrative files is still in the form of hard files, so it is less effective because it results in several risks, such as file loss and difficulty in searching for files, if needed. This study builds a decision support system using the Combinative Distance-Based Assessment (CODAS) method to recommend consulting service partners. The application of the CODAS method uses 3 criteria, 6 sub-criteria, and 19 sub-criteria. The results of calculations using the CODAS method are sorted from the highest value to the lowest value. From the 30 alternative data used, the first rank is A1 with a value of 4.6217, the second rank is A23 with a value of 4.3527, and the third rank is A27 with a value of 4.2107. Of the 30 alternative data used, the Spearman rank correlation value of 0.9973 is included in the very high positive category